Frequency in a slaughterhouse of seropositive pigs to Toxoplasma gondii from non-technical pig farms - Islachin H., Jhon (2016)
The aim of this study was to determine the frequency of pigs in a slaughterhouse with antibodies anti-Toxoplasma gondii from non-technical pig farms in Lima, Peru, and to assess the sex as a risk factor. Blood samples (n=240) were collected in a slaughterhouse in Lima (120 samples per sex) and the sera were analyzed by indirect immunofluorescence test (IIFT). The frequency of pigs with antibodies anti-T. gondii was 26.3%, with a confidence interval of 95% from 20.7 to 31.8%. In the analysis by sex, 26.3% of females and 30.8% of males were reactors to T. gondii. In the odds ratio test, the possible association of sex as a risk factor showed a non-significant value of 1.61.